From 3D to 4D printing: approaches and typical applications - Zhou, Ye; Huang, Wei Min; Kang, Shu Feng; Wu, Xue Lian; Lu, Hai Bao; Fu, Jun; Cui, Haipo (Journal of mechanical science and technology, 2015)
With the additional dimension, 4D printing is emerging as a novel technique to enable configuration switching in 3D printed items. In this paper, four major approaches, namely self-assembly of elements, deformation mismatch, bi-stability, and the Shape memory effect (SME), are identified as the generic approaches to achieve 4D printing. The main features of these approaches are briefly discussed. Utilizing these approaches either individually or in a combined manner, the potential of 4D printing to reshape product design is demonstrated by a few example applications.